Pengaruh Harga Promosi dan Kualitas Pelayanan terhadap Kepuasan Konsumen Kursus Mengemudi Mafaza Medan - Sofi Alfi Syahrin Br Milala; Awaludin; Oki Prayogi (Jurnal Manajemen DIVERSIFIKASI, 2025)
This research aims to comprehensively analyze the influence of promotional pricing andservice quality on customer satisfaction at Mafaza Driving Course in Medan. In thecompetitive driving course industry, a deep understanding of factors affecting customersatisfaction is vital for business sustainability and development. Using a quantitativeapproach with survey methodology, data was collected through questionnaires distributed to37 consumers who had participated in Mafaza Driving Course in July 2024. The results ofmultiple linear regression analysis show that promotional pricing has a positive andsignificant effect on customer satisfaction with a t-count value (3.652) > t-table (1.691) andsignificance of 0.001 < 0.05. Similarly, service quality also has a positive and significanteffect on customer satisfaction with a t-count value (6.063) > t-table (1.691) and significanceof 0.001 < 0.05. Simultaneously, both variables have a positive and significant effect oncustomer satisfaction with an F-count value (37.528) > F-table (3.34) and significance of0.001 < 0.05. The Adjusted R Square value of 0.670 indicates that 67% of the variation incustomer satisfaction can be explained by the promotional pricing and service qualityvariables. An important finding from this research is that service quality has a moredominant influence compared to promotional pricing, emphasizing the importance of servicequality improvement strategies in the driving course business.